2020
DOI: 10.1177/2040622320965067
|View full text |Cite
|
Sign up to set email alerts
|

Complement component 3 as biomarker of disease activity and cardiometabolic risk factor in rheumatoid arthritis and spondyloarthritis

Abstract: Objective: To analyze the relationship between complement component 3 (C3) and the prevalence of cardiometabolic risk factors and disease activity in the rheumatic diseases having the highest rates of cardiovascular morbidity and mortality: rheumatoid arthritis (RA), psoriatic arthritis (PsA) and axial spondyloarthritis (axSpA). Methods: This is a cross-sectional study including 200 RA, 80 PsA, 150 axSpA patients and 100 healthy donors. The prevalence of cardiometabolic risk factors [obesity, insulin resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…A number of recent studies highlight the impact of lipid metabolism on complement signalling pathways. For instance, complement factor C3 and C4 levels have been associated with cardiometabolic risk factors such as obesity and insulin resistance ( Arias de la Rosa et al, 2020 ), fat distribution ( Fu et al, 2020 ), and metabolic syndrome and diabetes ( Copenhaver et al, 2020 ) in humans. In animal studies, findings have also demonstrated that peptide antagonists of complement receptors C3aR and C5aR inhibited diet-induced obesity, adipose inflammation, and metabolic dysfunction in rats and ameliorated inflammatory responses in murine macrophages ( Lim et al, 2013 )—a topic reviewed by Barbu et al (2015) .…”
Section: Lipids In Alzheimer’s Diseasementioning
confidence: 99%
“…A number of recent studies highlight the impact of lipid metabolism on complement signalling pathways. For instance, complement factor C3 and C4 levels have been associated with cardiometabolic risk factors such as obesity and insulin resistance ( Arias de la Rosa et al, 2020 ), fat distribution ( Fu et al, 2020 ), and metabolic syndrome and diabetes ( Copenhaver et al, 2020 ) in humans. In animal studies, findings have also demonstrated that peptide antagonists of complement receptors C3aR and C5aR inhibited diet-induced obesity, adipose inflammation, and metabolic dysfunction in rats and ameliorated inflammatory responses in murine macrophages ( Lim et al, 2013 )—a topic reviewed by Barbu et al (2015) .…”
Section: Lipids In Alzheimer’s Diseasementioning
confidence: 99%
“…C1q serum levels have been shown to correlate with clinical disease activity ( Holers and Banda, 2018 ), whereas MBL serum levels have been associated with a favourable outcome ( Garred et al, 2000 ). More recently, RA patients have been found to present higher plasma levels of C2, C3a and sC5b9 compared to control subjects, suggesting a potential activation of the classical pathway ( Bemis et al, 2019 ; Arias de la Rosa et al, 2020 ). Higher levels of C3b/iC3b, a split product of C3, and factor I were also reported in female compared to male patients, suggesting a counter regulatory mechanisms in women, who are more prone to develop RA ( Bemis et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, among patients with RA, C3 has emerged as marker of metabolic disease: increased C3 was associated with insulin resistance in both obese and non-obese subjects ( Ursini et al, 2017a ), accurately identifying patients with type 2 diabetes ( Ursini and Abenavoli, 2018 ) and fatty liver disease ( Ursini et al, 2017b ). Very recently, in a cohort of 200 RA patients, de la Rosa and colleagues reported increased C3 to be associated with cardiometabolic risk and high disease activity at cluster analysis ( Arias de la Rosa et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations